Coronavirus Disease 2019 Policy Restricting Family Presence May Have Delayed End-of-Life Decisions for Critically Ill Patients. Issue 10 (October 2021) - Azad, Tej D.; Al-Kawaz, Mais N.; Turnbull, Alison E.; Rivera-Lara, Lucia
Abstract : OBJECTIVES: To determine if a restrictive visitor policy inadvertently lengthened the decision-making process for dying inpatients without coronavirus disease 2019. DESIGN: Regression discontinuity and time-to-event analysis. SETTING: Two large academic hospitals in a unified health system. PATIENTS OR SUBJECTS: Adult decedents who received greater than or equal to 1 day of ICU care during their terminal admission over a 12-month period. INTERVENTIONS: Implementation of a visit restriction policy. MEASUREMENTS AND MAIN RESULTS: We identified 940 adult decedents without coronavirus disease 2019 during the study period. For these patients, ICU length of stay was 0.8 days longer following policy implementation, although this effect was not statistically significant (95% CI, –2.3 to 3.8; p = 0.63). After excluding patients admitted before the policy but who died after implementation, we observed that ICU length of stay was 2.9 days longer post-policy (95% CI, 0.27–5.6; p = 0.03). A time-to-event analysis revealed that admission after policy implementation was associated with a significantly longer time to first do not resuscitate/do not intubate/comfort care order (adjusted hazard ratio, 2.2; 95% CI, 1.6–3.1; p < 0.0001). CONCLUSIONS: Policies restricting family presence may lead to longer ICU stays and delay decisions to limit treatment prior to death. Further policy evaluation and programs enabling access to family-centered care and palliative care during the ongoing coronavirus disease 2019 pandemic are imperative. Abstract : Supplemental Digital Content is available in the text.